Stroke Revisited: Diagnosis and Treatment of Ischemic Stroke - Lee, Seung-Hoon (Springer Singapore : Imprint: Springer, 2017)
This book presents state of the art knowledge on stroke management in a unique organizational style. Ischemic stroke is extensively covered, with inclusion of overviews that dynamically describe all relevant diagnostic and therapeutic processes in a time sequence mirroring real practice. The individual components of management and key issues are fully discussed with the aid of complementary illustrations that facilitate understanding of practical aspects and enable the reader to retrieve fundamental information quickly. In addition, the book considers the various causes of stroke and provides detailed guidance on means of secondary prevention. The recent demonstration of the substantial benefit of intra-arterial thrombectomy using stentrievers in patients with acute ischemic stroke represents a great moment in the history of stroke management. As we embark on a new era, there is an urgent need to review and evaluate current modalities for stroke diagnosis and treatment. In tackling this task, this book will be invaluable for physicians, angiographic interventionists, surgeons, and students seeking to acquire up-to-date knowledge on stroke.
Keywords: Medicine.; Radiology.; Neurology.; elektronické knihy; electronic books